Regulation, Rents and "Iconic Design": rent acquisition by design in the tightly constrained London office market - Paul Cheshire; Gerard Dericks (European Regional Science Association (ERSA), 2013)
A 2008 paper investigating the Regulatory Tax (RT) on office development in Britain (Cheshire & Hilber, 2008) provided evidence of very tight restrictions on office space going back at least 50 years. It was also argued that the RT measure tended to underestimate the full costs of restrictive land use regulation since compliance costs would be under estimated. One form of compliance cost could be rent seeking by employing ?expensive design and a trophy architect? to get ?more rentable space per unit area of the site?. This paper finds evidence strongly supportive of this hypothesis and then values the contribution of famous architects to flexing one of the most restrictive planning systems in the world. It uses a sample of transactions in London offices sold between 2000 and 2011 courtesy of the Estates Gazette and Real Capital Analytics supplemented with GIS and building specific data. Trophy architects are identified as those who have won a prize from one of the three major architectural bodies. We employ a hedonic approach and show that i) given the site size a building designed by a trophy architect is more valuable than one designed by a regular architect, but that ii) this arises because such buildings do indeed squeeze more space on a given sized site than those designed by ordinary architects; however iii) the price per m2 of a trophy architect?s building is no greater; that iv) the value of a trophy architect has emerged since 1956 and v) buildings designed by trophy architects predating the introduction of the current planning system are less valuable for a given site.
Keywords: H3; J6; Q15; R52; 330; Land use regulation; regulatory costs; rent seeking; office markets